Problems of accounting for value added tax in the republic of Uzbekistan - Djalilov Rakhmonkul Hamidovich; Alimova Komila (THE INNOVATION ECONOMY, 2026)
This scientific article presents value added tax, its place in the tax system of our republic and foreign countries, and the stages of its development. It is based on the need to adopt a single value-added tax rate.